The Effectiveness of Semantic Therapy on Death Anxiety, Pain Catastrophizing, Chronic Pain Acceptance, and Pain Intensity in Patients with Breast Cancer - Nathera Hussin Alwan; Kahtan A. Mohammed; Abdullah Shakir; Mohammed Kadhim Abbas Al-Maeeni; Mostafa Hsan Elwan; Nazar Abd-Al-Gaffar Rsen; Maytham T. Qasim (International Journal of Body, Mind and Culture, 2023)
Background: Breast cancer is the most emotionally and psychologically affecting cancer among women, causing the patient to experience profound emotional and psychological difficulties. The present study aimed to examine the effectiveness of semantic therapy on death anxiety, pain catastrophizing, chronic pain acceptance, and pain intensity in patients with breast cancer.